Sistema de gestión de un gimnasio mediante una aplicación android y el uso de tecnología biométrica para la administración de datos de los usuarios. - Chicaiza Ramírez, Jonathan Pablo (2017)
This research project is focused on eradicating the problem in the gym “EXTREME GYM”, located in Ambato city Tungurahua Province. The problem stems from not being able to take full management of the clients, the gym does not have the appropriate technology to automate this process and resulting in economic losses for their owners. For this problem, together with the owner of the gym, the implementation of a technological solution has been viable, considering that the automation of processes and the management of database will allow generating and analyzing the information, also helping your clients to complete their routines already programmed according to how each coach catalogs them, taking care of their health and avoiding excesses. In the development of the mobile application, Android Studio was used, which optimizes monthly payment times. In the research development, the deductive method was applied through the use of techniques such as the survey, interview and observation. Based on these, the real problems are understood and analyzed. The mobile application has been developed based on the Mobile-D methodology that provides quick results characterized by working with small groups. In the web application, the Scrum methodology was used, generating better communication between the client and the development team, allowing greater productivity and system quality. Finally, the implementation of the mobile application has benefited the gym "Extreme Gym" when managing user information.